Relasi Kompetensi Profesional Guru terhadap Peran Keteladanan di SMA Laboratorium Unsyiah Kota Banda Aceh - Rizki Maulana; Zulfatmi Zulfatmi; Muji Mulia (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The professional competence of teachers has not been able to change students' morals for the better. Usman argued that teachers have an important role, and are responsible for shaping the character of their students. The teacher is an important factor that has a big influence on the success of character education in schools. Facts in the field, there are still many teachers who do not have good competence. One of the competencies that need to be highlighted is the professional competence possessed by a teacher. This study aims to determine the professional competence of teachers at SMAS Laboratorium School Unsyiah; knowing the role of exemplary teachers in the Unsyiah School Laboratory SMAS; knowing the relationship of teacher professional competence to the role of exemplary at SMAS Laboratory School Unsyiah Banda Aceh City. The method used in this research is qualitative method. with interview data collection techniques, documentation, observation. There are 3 findings in this study; first, the professional competence of teachers at the Unsyiah School Laboratory High School; second, the role of exemplary teachers in the Unsyiah School Laboratory SMAS; the third is the relationship of teacher professional competence to the role of exemplary at SMAS Laboratorium School Unsyiah. This finding can be used to strengthen data on the relation of teacher professional competence to the role of exemplary. Based on these results, it can be concluded that the professional competence of teachers is very closely related in the process of setting an example for students, so that students will tend to be easy to advise.